Cephalometric analysis of a new method for the treatment of anterior open bite cases - Abdullatif, Husam (My University, 2001)
Anterior open bite çözümlenmesi zor ve karmaşık bir malokluzyondur. Etyolojisi hakkında bir çok teori üretilmiş ve tedavisi için bir çok tedavi yöntemi denenmiştir. Çeşitli habit breaker apereyleri, fonksiyonel apereyler, bite bloklar ve sabit ortodontik apereyler kullanılmıştır. Bütün bu yaklaşımlara rağmen open bite, tedavisi ve retansiyonu zor bir durum olarak kalmıştır. Keser ekstruzyonunun geri döndüğü ve estetik olmadığı ve molar intruzyonu elde etmenin zor olduğu ispatlanmıştır. Bu çalışmadaki amacımız, open bite vakalarının tedavisini molarları intruze ederken, ön dişleri aksi yönde etkilemeden tedavi etmeye çalışmaktır. Bu mandibulanın yukarı ve öne doğru rotasyonunu sağlayacak ve böylece open bite azalacaktır. Aynı zamanda ön bölgede daha az oluşacak olan extruzyon, daha iyi bir estetiğe ve stabilizasyona sebep olacaktır. Yaş ortalamaları 13.94 olup, en büyüğü 16 en küçüğü 12.75 olan, 4 erkek ve yaş ortalamaları 12.36 olup, en büyüğü 14 en küçüğü 10 yaşında olan, 4 kız, toplam 8 hasta özel olarak dizayn edilmiş bir aperey ile tedavi edildi. Aperey olarak, premolarların bukkalinde metal tüp bulunan, tüm dentisyonu kaplı modifiye akrilik cap splint ekpansiyon apereyi kullanıldı. Bir face bow kullanılmıştır. Face bowun iç kolları bukkal tüplere girecek şekilde, dış kolları ise dentoalveolar komplexin altına gelecek şekilde aşağıya doğru, özel bir şekilde sonlandırılarak, büküldü. Bir oksipital headgear vasıtasıyla distal ve yukarı yönlü kuvvet uygulandı. Bu özel dizayn tüm maksillaya intruzyon kuvveti uygularken, oluşan saat yönünün tersine moment, intruzyonun posterior bölgede gerçekleşmesini, anterior bölgenin ise palatinale devrilmesini ve ekstruzyon oluşmasını sağlamıştır. Tedavi 1 haftalık rapid palatal ekspansiyon işlemi ile başlamış ve head gear uygulaması ile devam etmiştir. Aparey 6 ay kullanıldıktan sonra sabit ortodontik tedaviye geçilmiştir. Tedavinin başlangıcında ve aperey çıkartıldıktan sonra gerekli kayıtlar alınmıştır. SN/ MP açısında 1.44° lik bir azalma gözlenmiştir (P<0.05). Üst okluzal düzlem ile SN arasındaki açı (UOP/ SN), molar intruzyonuna ve göreceli keser ekstruzyonuna bağlı olarak 6.88° (P<0.01) artmıştır. Anteriorda, posteriorda ve alt yüz yüksekliğinde belirgin bir değişiklik görülmemiştir. SNB açısı 0.69° (p<0.05) artmıştır. Üst keserler SN düzlemine göre ortalama 6.38° (P<0.01) palatinale devrilirken, tedavi sonunda belirgin bir ekstruzyon kaydedilmemiştir. Üst birinci molar 2.81mm (P<0.01), üst ikinci molar ise 2.13mm (P<0.05) intruzyona uğramıştır. Üst keserler 2.63mm (P<0.01) distale hareket ederken, üst birinci molarlar 1.75mm (P<0.05), üst ikinci molarlar ise 1.56mm (P<0.05) distale gitmiş ve sagital ilişkinin düzelmesine yardımcı olmuştur. Yaş ortalamaları 11.86 olan 7 hasta, kontrol grubu olarak kullanıldı. Bu hastalardan; yaş ortalamaları 11.6 olan 4 tanesi kız , yaş ortalamaları 12.2 olan 3 tanesi ise erkekti. Bu gruptaki hastalara hiçbir tedavi uygulanmaksızın 6 ay takip edildiler ve 6. ayın sonunda tedavi grubunda kullanılan ölçümler kullanılarak analiz leri yapıldı. Sonuç olarak, kesici dişlerde belirgin bir extruzyon oluşmadan, molarlarda extruzyon elde edilmiştir. Ayrıca, biteın kapanmasına ve sınıf II malokluzyonun düzelmesine yardımcı olan, mandibulanın yukarı ve ileri rotasyonu sağlanmıştır. Bu çalışmanın amacına ulaştığı inancında olmakla birlikte, bu apereyle tedavi edilmiş hasta sayısının arttırılması ve bu vakaların tedavi sonrası uzun dönem sonuçlarının takip edilmesi gerekmektedir.

CEPHALOMETRIC ANALYSIS OF A NEW METHOD FOR THE TREATMENT OF ANTERIOR OPEN BITE CASES Anterior open bite is a complex and confusing condition in orthodontics. Many theories about its etiology have been developed. And many treatment modalities, like various habit breaking appliances, functional appliances, bite blocks, and fixed orthodontic appliances have been used to treat this malocclusion. Despite all these approaches, open bite has still remained a difficult condition to treat and to retain. Molar intrusion proved to be difficult to attain, and incisor extrusion was unaesthetic and unstable. Our aim in this study was attempt to treat anterior open bite by intruding the maxillary molars while not adversely affecting the anterior teeth. We would expect the mandible to rotate upward and forward and thus the open bite will decrease. At the same time, less extrusion in the anterior area would mean better stability and esthetic results. Eight patients with a total average age of 13.15 years, 4 males, with an average age of 13.94 years. And 4 female patients, with an average age of 12.36 years were treated with a specially designed appliance. The appliance was a modified full coverage acrylic cap splint expansion appliance, with tubes at the premolar buccal area on both sides. A face bow was used. The inner bows of the face bow were inserted in the buccal tubes and the outer bows were bent inferiorly and ended under the center of resistance of the maxillary dentoalveolar complex. The force was applied from an occipital head gear with an upward and distal direction. This special design ensured an intrusion force on the maxilla and a clockwise moment which intrudes posterior teeth, while retroclining and extruding anterior teeth. Treatment started with one week of rapid palatal expansion followed by the application of the head gear. The appliance was used for 6 months, followed by fixed orthodontic treatment. Necessary records were taken at the onset of the treatment and after the removal of the appliance. A control group consisiting of 7 patients with an average age of 11.86 years was used. 4 of these were females with an average age of 11.6 and 3 were males with an average age of 12.2. They were followed up without any treatment for 6 months and were analysed and studied using the same measurements used in the treatment group. In the treatment group a decrease of 1.44° in the SN/ MP angle was noticed (P<0.05). The angle between the Upper Occlusal Plane and SN (UOP/ SN), increased an average of 6.88° (P<0.01) due to clockwise rotation of maxillary dentition. No significant changes in the anterior, posterior, and lower facial height was seen. SNB angle increased 0.69° (p<0.05). The upper incisor was retroclined in respect to SN plane by an average of 6.38° (P<0.01), while it was not extruded significantly after the treatment. The upper first molars intruded 2.81mm (P<0.01) on average and the second molars also intruded 2.13mm (P<0.05). The upper incisor was moved distally an amount of 2.63mm (P<0.01). Thus, the overbite was increased by this method an average of 3.75mm (P<0.01). The overjet also decreased by 3.94mm (P<0.01). As for the changes in the control group, no important significant changes were observed other than an increase in the anterior and posterior facial heights of 1.71 and 1.77mm respectively (P<0.05) and an eruption and extrusion as recorded by the increase of U1-TH of 1.57mm (P<0.05) and an increase in U7-TH of 2mm (P<0.05) In conclusion, Intrusion of molars without significant extrusion of the incisors was achieved. Mandibular upward and forward rotation also was observed which helped in closing the bite and contributed to the treatment of the class II condition. We believe that this study has achieved its aim, but it remains important to increase the number of patients treated with this appliance, study them and follow up the cases and results for a long time after end of treatment.
Keywords: DİŞ HEKİMLİĞİ-TEDAVİ; ORTODONTİ